2014
DOI: 10.20855/ijav.2014.19.3354
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Multiple Perforated Plate Sound Absorber Made of Coir Fiber

Abstract: Current studies are aiming to improve the sound absorption of coir fiber by implementing combinations of Perforated Plates (PPs) and air gaps. The Atalla and Sgrad model along with Johnson-Allard model and Acoustic Transmission Analysis (ATA) approach are used to estimate the absorption coefficient of the combination. Measurements are conducted in impedance tube to validate the analytical results. Outcomes show that the absorption coefficient of the panel is governed by the porosities of the implemented PPs. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The result was that this material could be used in commercial automotive mufflers [19]. Similar to the MPP, multi layer absorbers supported by the Helmholtz resonator and compartment cavities were developed by Ayub et al and Kidner and Hansen [20,21]. The design of absorber is an approach that gives benefits not only in the absorption shift to a lower band, but also in improving MPP performance in the medium-high frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…The result was that this material could be used in commercial automotive mufflers [19]. Similar to the MPP, multi layer absorbers supported by the Helmholtz resonator and compartment cavities were developed by Ayub et al and Kidner and Hansen [20,21]. The design of absorber is an approach that gives benefits not only in the absorption shift to a lower band, but also in improving MPP performance in the medium-high frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…It was found to be an effective filler in the fiber matrix composite, improving the mechanical properties of the materials. 15 Ayub et al 16 successfully evaluated the sound absorption coefficient of multiple perforated plate sound absorber made of coconut coir fiber. Their investigation confirmed that a decreased porosity promotes the sound absorption performance of a composite in the low-frequency region.…”
Section: Novel Implementation Of Natural Fibro-granular Materials As mentioning
confidence: 99%
“…Current analytical models for the prediction of the sound absorption coefficient can provide accurate results over large operating ranges, but they are highly complex and require comprehensive experimental testing to determine many variables [1]. This is often not feasible to use in practical applications [2].…”
Section: Introductionmentioning
confidence: 99%